Primary Pleomorphic Adenoma of the External Auditory Canal: A Case Report and Review of the Literature - Chizu Saito; Takeharu Kanazawa; Takehiko Yamaguchi; Ken-ichi Nakamura; Keiichi Ichimura (Case Reports in Otolaryngology)
Background. Pleomorphic adenoma (PA) is a benign tumour that mainly arises from salivary glands, and PA of the external auditory canal (EAC) is very rare. The objective of this study was to clarify the clinical presentation and treatment of PA of the EAC. Method. The authors present a case of PA arising from the EAC together with a literature review. Results. A 40-year-old man complained of hearing loss and foreign-body sensation of the right ear. Clinical and radiological examinations revealed a well-defined tumour limited to the EAC, with no connection to the parotid gland. Preoperative fine-needle aspiration cytology findings were characteristic of PA. The tumour was removed en bloc with the overlying skin. Conclusion. PA of the EAC is very rare, and methods to rule out malignancy before treatment are lacking. Thus, long-term follow-up is necessary, because malignant tumours are common in the EAC and PA has malignant potential.